Research and realization of the Trojan detection engine based on Android - Bin XIA; Feng QIU (Dianxin kexue)
During recent years, Trojan viruses on Android systems have greatly evolved, and the frequent security breach of Android systems is rapidly becoming a great concern of contemporary cyber security. The study of Trojan virus detection on Android engine and the application of its outcome has become increasingly significant. A feature code detection algorithm called FCPA got the sourceDir of the known malicious APK files through calling system API. It uses hash algorithm to process these files in order to get the feature information of the files so that the eigenvalue could got which could identify Trojan uniquely. The feature code library was composed of these eigenvalues. The Trojan detection engine called TDE, with the assistance of this feature code library, would be able to take out a quick scan among the files in the cell phone and detect malicious programs in mobile applications. Finally, the designed Trojan detection engine provided a secure environment for the user of the phone.